Lego DC Batman. Family matters [videorecording (Blu-Ray + DVD)] - Adams, Jeremy (Screenwriter); Kelly, Tim, 1958- (Warner Bros. Home Entertainment, 2019)
After receiving mysterious invitations, Batman and his team encounter the villainous Red Hood, who is obsessed with destroying the Bat-family and all of Gotham City.